Two new species of Fusicolla (Hypocreales) from China - Liu, Chang; Zhuang, Wen-Ying; Yu, Zhi-He; Zeng, Zhao-Qing (Phytotaxa, 2022)
Two new Fusicolla species are described and illustrated based on strains isolated from soil and rotten twig. Morphological features and DNA sequence analyses of combined ITS and LSU regions support their placements in Fusicolla and recognition of new species. Fusicolla gigas sp. nov. is characterized by C-shaped, 0−4(−5)-septate microconidia, falcate, (1–)4–9-septate macroconidia up to 80 µm long, and pinkish orange colonies on PDA. Fusicolla guangxiensis sp. nov. is distinguished by long-fusiform, falcate, (0–)1(–3)-septate macroconidia with acute ends, and orange colonies on PDA. Their macroconidia produced on OA are obvious larger than those on PDA. Distinctions between the new species and their close relatives are compared in detail.